Trehalose and glucose levels regulate feeding behavior of the phloem-feeding insect, the pea aphid Acyrthosiphon pisum Harris - Guang Wang (Nature Portfolio, 2021)
Abstract Trehalose serves multifarious roles in growth and development of insects. In this study, we demonstrated that the high trehalose diet increased the glucose content, and high glucose diet increased the glucose content but decreased the trehalose content of Acyrthosiphon pisum. RNA interference (RNAi) of trehalose-6-phosphate synthase gene (ApTPS) decreased while RNAi of trehalase gene (ApTRE) increased the trehalose and glucose contents. In the electrical penetration graph experiment, RNAi of ApTPS increased the percentage of E2 waveform and decreased the percentage of F and G waveforms. The high trehalose and glucose diets increased the percentage of E2 waveform of A. pisum red biotype. The correlation between feeding behavior and sugar contents indicated that the percentage of E1 and E2 waveforms were increased but np, C, F and G waveforms were decreased in low trehalose and glucose contents. The percentage of np, E1 and E2 waveforms were reduced but C, F and G waveforms were elevated in high trehalose and glucose contents. The results suggest that the A. pisum with high trehalose and glucose contents spent less feeding time during non-probing phase and phloem feeding phase, but had an increased feeding time during probing phase, stylet work phase and xylem feeding phase.